Sosialisasi Peningkatan Pemahaman Masyarakat Sebagai Upaya Penurunan Stunting Menuju Pembangunan Berkelanjutan (SDGs) - Krisnaningsih, Erni; Dwiyatno, Saleh; Masyruroh, Anis; Sulistyo, Arif Budi; Gunawan, Wawan; Nuryusuf, Muhammad Rifki; Destiana, Dina; Chayadi, Dadi; Sulistiyono, Sulistiyono; Ramadhan, Muhammad Denis (ABDIKARYA: Jurnal Pengabdian dan Pemberdayaan Masyarakat, 2023)
Stunting is a problem that has national and international implications. Stunting is a chronic nutritional problem that occurs when children experience stunted growth due to chronic malnutrition at critical periods, especially during the first 1,000 days of life, starting from pregnancy to age two. One of them is the need to prevent and reduce stunting rates by conducting Community Service (CS) activities by socializing with the community. PKM activities aim to increase community understanding to reduce stunting towards sustainable development (SDGs) through socialization activities in Sukamaju village, Cikeusal sub-district. CS activities consist of four stages: Identification of needs, Preparation, Socialization, and Evaluation. The results of PKM activities generally went well, and there was an increase in community understanding after participating in socialization activities. Stunting prevention is not a short-term effort; its impact will only be seen in the long term. Therefore, policymakers must have a solid long-term vision and patience in seeing the results that will be achieved to support sustainable development and the welfare of future generations